2014
DOI: 10.2478/s11536-013-0331-x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence in adolescent females with cystic fibrosis in Poland

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…reported that many women felt UI affected their social life, school/work and intimate relationships ‘a lot’ or ‘most of the time’ (range: 29–42%). More than half of the sample also reported that UI affected their holidays, social life, school/work and interests/hobbies ‘a little bit’ or ‘a fair bit’ (50–58%) . A report by Moran et al .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…reported that many women felt UI affected their social life, school/work and intimate relationships ‘a lot’ or ‘most of the time’ (range: 29–42%). More than half of the sample also reported that UI affected their holidays, social life, school/work and interests/hobbies ‘a little bit’ or ‘a fair bit’ (50–58%) . A report by Moran et al .…”
Section: Resultsmentioning
confidence: 99%
“…Both increasing age and lower FEV 1 were significantly associated with UI frequency. A study of 64 young Polish women with CF (mean ± SD age: 20.9 ± 1.5 years) found that 44% experienced UI . The majority (86%) reported UI more than once per year, with 58% endorsing moderate severity of incontinence (defined as ‘wet/a small amount’).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations